Abscisic acid agonists suitable for optimizing plant water use - Roeder, Jan; Liu, Jinghui; Doch, Isabel; Ruschhaupt, Moritz; Christmann, Alexander; Grill, Erwin; Helmke, Hendrik; Hohmann, Sabine; Lehr, Stefan; Frackenpohl, Jens; Yang, Zhenyu (Frontiers in Plant Science, 2023)
Climate change and overexploitation of groundwater resources cause constraints on water demand for agriculture, thus threatening crop productivity. For future food security, there is an urgent need for crops of high water use efficiency combined with high crop productivity, i.e. having high water productivity. High water productivity means efficient biomass accumulation at reduced transpiration. Recent studies show that plants are able to optimize carbon uptake per water transpired with little or no trade-off in yield. The phytohormone abscisic acid (ABA) plays a pivotal role in minimizing leaf transpiration and mediating enhanced water productivity. Hence, ABA and more chemically stable ABA agonists have the potential to improve crop water productivity. Synthesis, screening, and identification of suitable ABA agonists are major efforts currently undertaken. In this study, we used yeast expressing the plant ABA signal pathway to prescreen ABA-related cyano cyclopropyl compounds (CCPs). The yeast analysis allowed testing the ABA agonists for general toxicity, efficient uptake, and specificity in regulating different ABA receptor complexes. Subsequently, promising ABA-mimics were analyzed in vitro for ligand-receptor interaction complemented by physiological analyses. Several CCPs activated ABA signaling in yeast and plant cells. CCP1 and CCP5 were by an order of magnitude more efficient than ABA in minimizing transpiration of Arabidopsis plants. In a progressive drought experiment, CCP2 mediated an increase in water use efficiency superior to ABA without trade-offs in biomass accumulation.